2008
DOI: 10.1038/nrc2402
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent gene fusions in prostate cancer

Abstract: The discovery of recurrent gene fusions in a majority of prostate cancers has important clinical and biological implications in the study of common epithelial tumors. Gene fusion and chromosomal rearrangements were previously thought to be the primary oncogenic mechanism of hematological malignancies and sarcomas. The prostate cancer gene fusions that have been identified thus far are characterized by 5' genomic regulatory elements, most commonly controlled by androgen, fused to members of the ETS family of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
544
3
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 617 publications
(591 citation statements)
references
References 111 publications
22
544
3
13
Order By: Relevance
“…Extensive efforts have been focused on further elucidation of the biological basis of CaP onset/progression that may lead to the development of new diagnostic and prognostic markers, and identification of potential therapeutic targets. [4][5][6] Alterations in the expression of chromosome 8 genes (losses at 8q21-22 and amplifications at 8q24) have been identified in CaP. 7 Amplification at the 8q24 locus, which includes the C-MYC proto-oncogene, has been suggested as potential prognostic factor for CaP.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive efforts have been focused on further elucidation of the biological basis of CaP onset/progression that may lead to the development of new diagnostic and prognostic markers, and identification of potential therapeutic targets. [4][5][6] Alterations in the expression of chromosome 8 genes (losses at 8q21-22 and amplifications at 8q24) have been identified in CaP. 7 Amplification at the 8q24 locus, which includes the C-MYC proto-oncogene, has been suggested as potential prognostic factor for CaP.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,7 Subsequent studies have found these gene fusions to appear early in prostate cancer development, 6 present in a subset of cases of prostatic intra-epithelial neoplasia and putative precursor lesions. 2,8,9 Likewise, ERG fusions are present throughout the spectrum of the various microscopic manifestations of prostate cancer, 6,10,11 supporting their role as a key step in the pathogenesis of prostate cancer in general. However, other genetic alterations appear to be contributory components of tumor development, such as loss of PTEN and activation of the PI3-kinase pathway, particularly in the setting of progression from an intraepithelial neoplasm to invasive adenocarcinoma.…”
mentioning
confidence: 94%
“…[1][2][3][4][5][6] Most commonly, fusion of the transcriptional regulator gene ERG (ETSrelated gene) with TMPRSS2 is seen, present in half or more of prostate cancers, although other partner genes, such as ETV1, ETV4 and ETV5, may be involved in translocations. 1,2,7 Subsequent studies have found these gene fusions to appear early in prostate cancer development, 6 present in a subset of cases of prostatic intra-epithelial neoplasia and putative precursor lesions.…”
mentioning
confidence: 99%
See 2 more Smart Citations